Expression of Aquaporin Water Channels in Equine Endometrium is Differentially Regulated During the Oestrous Cycle and Early Pregnancy. Issue 4 (26th October 2012) - Klein, C; Troedsson, MHT; Rutllant, J
Contents: The expression of 12 different aquaporin subtypes in equine endometrium was examined at the mRNA and protein level. Endometrial samples were obtained during anoestrus, oestrus, 8, and 14 days after ovulation in non‐pregnant mares, and 14 days after ovulation in pregnant mares. Quantitative PCR revealed a time‐dependent pattern for all aquaporin subtypes examined except for AQP10 and 12 . AQP3, 5 and 7 showed highest mRNA abundance 8 days after ovulation, while AQP0 and 2 were most abundant at Day 14 of the cycle in non‐pregnant mares. At 14 days of pregnancy, AQP1, 4, 8, 9 and 11 displayed highest expression levels. Western blot analysis confirmed protein expression of AQP0, 2 and 5. Immunohistochemistry localized protein expression to luminal and glandular epithelial and stromal cells. AQP0 staining intensity was highest in samples obtained on Day 14 of the oestrous cycle. AQP2 immunoreactivity seemed to be stronger in samples collected 14 days after ovulation from non‐pregnant animals, in particular luminal epithelial staining. Samples collected 8 days after ovulation from cyclic animals were characterized by intense AQP5 staining of glandular epithelium, predominantly in the deeper glands. Progesterone treatment of anoestrous mares did not enhance expression of AQPs, indicating that factors other than progesterone are required for the up‐regulation of certain AQP subtypes during dioestrus. In conclusion, it seems that an equine‐specific collaboration of aquaporin subtypes contributes to changes in endometrial fluid content occurring throughout the oestrous cycle and contributes to endometrial receptivity during early pregnancy in the mare.